The Effect of Ethanol Extracts of Jeruju (Holy Mangrove) Leaves (Acanthus ilicifolius L.) and Taurine on Hematopoiesis Profiles of Mice (Mus musculus L.) Induced by Alloxan - Ardiansyah, Budi Khoiri; Widiastuti, Endang Linirin; Nurcahyani, Nuning; Sutyarso, Sutyarso (Jurnal Natur Indonesia, 2020)
The high exposure to free radicals and glucose blood levels in diabetes potentially damage the body cells and decrease body immune status that is shown by changes in the number of blood cells that can cause complications. The purpose of this research was to study the effect of ethanol extracts of jeruju (holy mangrove) leaves (Acanthus ilicifolius L.) and taurine on hematopoiesis profile by measuring the number of erythrocytes, the number of leukocytes and the leukocytes differential. This research used a Completely Randomized Design (CRD) by 5 treatments with 5 repetitions conducted for 14 days. The treatment groups were: K1 negative control, K2 positive control (alloxan induced only), P1 induced by alloxan and given 100% ethanol extract of jeruju leaves at dose of 22.4 mg/bb/day, P2 induced by alloxan and given 50% ethanol extract of jeruju leaves dose of 22.4 mg/bb/day, and P3 induced by alloxan and given taurine dose of 15.6 mg/bb/day. Data were analyzed by ANOVA and followed by LSD test at the 5% level. The results showed that the administration of jeruju and taurin can maintain the number of leukocytes and the number of lymphocyte cells that were close to normal after induced by alloxan. But has no effect in the number of erythrocytes in mice